Enhancing Trust and Transparency in Online Marketplaces Using Generative AI for Product Validation and Verification - Syed Rabeet; Mohammad Huzaifa Ghori; Talal Ahmed Siddiqi; Muhammad Habib; Syed Talha Ahmed (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2025)
The rise of online classified platforms has made buying and selling assets more convenient but has also introduced challenges related to trust, product authenticity, and misleading listings. This paper introduces SnapTrade, a next-generation classified platform that leverages Generative AI (GenAI) to enhance transparency and reliability in digital marketplaces. Unlike traditional platforms where buyers often receive products that do not match their descriptions, SnapTrade integrates AI-powered image analysis and product validation to ensure authenticity. Our empirical analysis reveals significant discrepancies between seller-provided ratings and AI-generated assessments (average difference of 1.57 points), with 23% of listings showing critical rating differences exceeding 3 points. The similarity analysis between user and AI-generated descriptions demonstrates that most listings (50%) have low content match scores (0.2-0.4), indicating AI’s ability to identify missing product information. Our cluster analysis further isolates high-risk transaction patterns, representing 27% of listings. By integrating Generative AI for rating verification and description enhancement, SnapTrade addresses core challenges of digital classifieds, providing a methodological framework for improving transparency and user trust in online marketplaces